Toward a high granularity and high counting rate, differential readout timing MRPC - Petriş, Mariana; Deppner, Ingo Martin; Herrmann, Norbert; Loizeau, Pierre-Alain (Nuclear instruments & methods in physics research. Section A, Accelerators, spectrometers, detectors and associated equipment, 2012)
A new differential architecture of a resistive plate counter based on high granularity strip structure readout electrodes, symmetric relative to the central anode, is proposed. Details of its design and construction are introduced. Results of the 60Co source tests and of the in-beam investigations using minimum ionizing particles are discussed. A time resolution of 50-60ps and a cluster size of ∼1.4 strips were obtained. These results together with previous ones based on low resistivity glass electrodes [1] open the perspective to built large area time-of-flight (TOF) detectors with a very good time resolution and high granularity for high intensity fixed target experiments.